Microbiological Diagnosis of Skeletal System Infections in Children - Yagupsky, Pablo (Current Pediatric Reviews, 2019)
Background: If not timely diagnosed and adequately treated, skeletal system infections in children may result in severe and permanent disability. Prompt identification of the etiology of the disease and determination of its antibiotic susceptibility are crucial for the successful management of septic arthritis, osteomyelitis, and spondylodiscitis. However, the bacteriological diagnosis of these infections has been traditionally limited by the low yield of conventional cultures and, on average, one-third of cases of pediatric joint and bone infections remained unconfirmed. Objective: To review the medical literature to summarize the current approach diagnosing the pediatric skeletal system infections. Methods: The relevant publications for the last three decades were reviewed. Results: In recent years, the detection of skeletal system pathogens has been revolutionized by the use of improved laboratory methods, including seeding of synovial fluid and bone exudates into blood culture vials, and the development and implementation of sensitive nucleic acid amplification assays. These advances have resulted in the recognition of Kingella kingae as the predominant etiology of hematogenous infections of bones, joints, intervertebral discs and tendon sheaths in children aged 6-48 months, and reduced the fraction of culture-negative osteoarthritis. Conclusion: As the exudate and tissue samples obtained from young children with skeletal system infections are frequently insufficient for a comprehensive laboratory workup, physicians should take in consideration the patient’s age, predisposing medical conditions and possible exposure to zoonotic organisms, and use a judicious combination of Gram’s stain, culture on blood culture vials, and molecular tests to maximize the microbiological diagnosis of these diseases.
Keywords: Children